(untitled) (Journal of Informatics Education and Research, 2025)
The (MSME) industry has developed as a thriving and dynamic segment of the Indian economy. MSMEs help in broadening economic activity, making significant contributions to manufacturing growth in both rural and urban areas, thus minimizing regional imbalances, ensuring a more equitable share of national revenue and assets, and promoting exports, with minimal capital necessities, operational flexibility, low intensive imports, the ability to develop desirable indigenous technology, substituted imports, involvement in defence manufacture, and technology-oriented The study’s major objective is to investigate the effect of NBFCs on MSMEs’ satisfaction with loan disbursement terms. It can be concluded that result is insignificant and there is no a significant difference in the level of satisfaction between micro and small entrepreneurs with regard to the terms of loan disbursements such as amount of loan, amount of loan, interest payable, collateral security for the loan, procedural formalities, documentation, sanctioned time, amount of instalments, schedule for repayment of each instalments, time lag between date of application and date of disbursements of loan and expenditure incurred in getting the loan.